A novel, cell-compatible hyaluronidase activity assay identifies dextran sulfates and other sulfated polymeric hydrocarbons as potent inhibitors for CEMIP - Schmaus, Anja; Spataro, Sofia; Sallmann, Paul; Möller, Stephanie; Scapozza, Leonardo; Prunotto, Marco; Sleeman, Jonathan P. (Cells, 2025)
Hyaluronan (HA) levels are dynamically regulated homeostatically through biosynthesis and degradation. HA homeostasis is often perturbed under disease conditions. HA degradation products are thought to contribute to disease pathology. The hyaluronidase CEMIP requires the presence of living cells for its HA depolymerizing activity. CEMIP is overexpressed in a variety of pathological conditions, and the inhibition of its hyaluronidase activity therefore has therapeutic potential. To identify novel inhibitors of the CEMIP hyaluronidase activity, we established here a cell-compatible, medium-throughput assay for CEMIP-dependent HA depolymerization. The assay employs ultrafiltration plates to separate low- from high-molecular-weight HA, followed by quantification of HA fragments using an HA ELISA-like assay. Using this assay, we tested a range of compounds that have been reported to inhibit other hyaluronidases. Thereby, we identified several sulfated hydrocarbon polymers that inhibit CEMIP more potently than other hyaluronidases. One of these is heparin, a sulfated glycosaminoglycan produced by mast cells that constitutes the first described physiological CEMIP inhibitor. The most potent inhibitor (IC50 of 1.8 nM) is dextran sulfate, a synthetic sulfated polysaccharide. Heparin and dextran sulfate are used in numerous established and experimental biomedical applications. Their ability to inhibit CEMIP needs to be taken into account in these contexts.
Titel des übergeordneten Special issue: Role of hyaluronan in human health and disease
Gesehen am 05.08.2025